1998
DOI: 10.1073/pnas.95.23.13899
|View full text |Cite
|
Sign up to set email alerts
|

ExoY, an adenylate cyclase secreted by thePseudomonas aeruginosatype III system

Abstract: The exoenzyme S regulon is a set of coordinately regulated virulence genes of Pseudomonas aeruginosa. Proteins encoded by the regulon include a type III secretion and translocation apparatus, regulators of gene expression, and effector proteins. The effector proteins include two enzymes with ADP-ribosyltransferase activity (ExoS and ExoT) and an acute cytotoxin (ExoU). In this study, we identified ExoY as a fourth effector protein of the regulon. ExoY is homologous to the extracellular adenylate cyclases of Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
414
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(427 citation statements)
references
References 38 publications
(33 reference statements)
9
414
0
4
Order By: Relevance
“…Type III secretion systems are found in many plant and human pathogens and are responsible for contact-dependent delivery of proteins into the cytoplasm of host cells. P. aeruginosa contains a single type III secretion system (PA1690±PA1725) which secretes several proteins including exoenzymes S, T and Y 24 .…”
Section: Annotation Of P Aeruginosa Genesmentioning
confidence: 99%
“…Type III secretion systems are found in many plant and human pathogens and are responsible for contact-dependent delivery of proteins into the cytoplasm of host cells. P. aeruginosa contains a single type III secretion system (PA1690±PA1725) which secretes several proteins including exoenzymes S, T and Y 24 .…”
Section: Annotation Of P Aeruginosa Genesmentioning
confidence: 99%
“…araD139 ∆(argF-lac)U169 rpsL150(Str R ) relA1 fibB 5301 deoC1 ptsF25 rbsR recA56 Gherardini et al (1990) P. aeruginosa strains PAK Laboratory strain (invasive) D. Bradley* PAKexsA ::Ω exsA knockout mutant derivative of PAK Yahr et al (1997) 1997 ;Hauser et al, 1998 ;Yahr et al, 1998 ;Vallis et al, 1999), the mechanisms by which these virulence factors alter mammalian cell physiology remain enigmatic.…”
Section: Se5000mentioning
confidence: 99%
“…Some virulence factors are produced and secreted directly into the host cell using the cell-contact-mediated type III secretion machinery. To date, four such factors have been characterized, including ADP-ribosylating enzymes ExoS and ExoT (Frank, 1997 ;Frithz-Lindsten et al, 1997 ;Yahr et al, 1996a), an acute cytolytic factor ExoU (Finck-Barbancon et al, 1997 ;Hauser et al, 1998) an adenylate cyclase ExoY (Yahr et al, 1998). Expression of these secreted effector molecules as well as components of the type III secretory apparatus are under the control of the transcriptional activator, ExsA (Hovey & Frank, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…ExoU possesses phospholipase A 2 and lysophospholipase activities (Phillips et al, 2003;Rabin & Hauser, 2005;Sato et al, 2003;Tamura et al, 2004) that lead to rapid lysis of mammalian cells (Coburn & Frank, 1999; Finck-Barbançon et al, 1997;Fleiszig et al, 1997;Hauser et al, 1998a;Vallis et al, 1999). ExoY is an adenylate cyclase that increases intracellular levels of cAMP (Yahr et al, 1998). Several studies have clearly demonstrated that the enzymic activities of ExoS, ExoT and ExoU contribute to pathogenesis by affecting bacterial persistence in infected tissues, bacterial dissemination and host survival (FinckBarbançon et al, 1997;Garrity-Ryan et al, 2000;Hauser et al, 1998a;Pankhaniya et al, 2004;Shaver & Hauser, 2004).…”
Section: Introductionmentioning
confidence: 99%